10.1016/s0029-7437(12)70152-0 (CrossRef Listing of Deleted DOIs, 2000)
OBJECTIVES: This scoping review aims to assess the current smoking cessation services provided by dental auxiliaries, the populations they serve and the barriers and facilitators they encounter in delivering these services. Additionally, it aims to inform evidence-based recommendations for delivering brief smoking cessation interventions by dental auxiliaries in primary healthcare settings. METHODS: Following the JBI scoping review methodology and the PRISMA-ScR checklist, we searched primary research, reviews and grey literature without restrictions on location, publication date, or language. Searches were conducted across five databases (PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Scopus, Web of Science, PsycINFO) and supplemented by an internet search for the grey literature. Two independent reviewers screened records for relevance, extracted data and categorised findings into tables. RESULTS: The initial search yielded 668 references, of which 141 were duplicates and 469 were excluded during the title and abstract screening stage. Fifty-eight studies underwent full-text assessment, and 15 were included in the review. The updated search identified 54 additional records. After the removal of three duplicates, 51 were screened, and all were excluded because they did not meet the inclusion criteria. Findings reveal that dental auxiliaries play an important role in smoking cessation within primary healthcare settings. The included intervention studies reported improvements in quit attempts, smoking reduction, abstinence rates and adherence to smoking cessation guidelines, particularly for interventions based on the 5A's model. Organisational support, training and access to smoking cessation resources facilitated intervention implementation. However, time constraints, inadequate reimbursement and patient-related barriers' attitudes remained the most reported barriers. CONCLUSION: This review highlights the critical role of dental auxiliaries in smoking cessation efforts and provides insights for developing targeted interventions. By addressing identified barriers and facilitators, interventions can be enhanced to support smoking cessation in primary dental care.